Novelties in Stigmatodon (Bromeliaceae, Tillandsioideae), a genus endemic to Brazil: three new species, one new combination, and two new stigma types - Leme, Elton M. C.; Couto, Dayvid R.; J. C. Kollmann, Ludovic; Nicoletti De Fraga, Claudio (Phytotaxa, 2022)
The authors describe, discuss, and illustrate three epilithic new species of Stigmatodon, S. ilhanus, S. itamarajuensis, and S. viridibracteatus, restricted to vertical rock walls in inselbergs located in the states of Bahia and Espírito Santo, Brazil, and propose a new combination, transferring the endemic Vriesea vexata from rupestrian fields in Minas Gerais state to Stigmatodon. The stigma morphology of Stigmatodon, which is one of the most important distinctive features of this genus, is reevaluated and illustrated, with the recognition of two new types, the convolute-blade type III (stigmadontoid type) and the tubo-laciniate type II. These new stigma types suggest a morphological bridge between the typical tubo-laciniate type I and the convolute-blade types I and II and represent a relevant progress in understanding the morphological boundaries of Stigmatodon.